Effect of information technology success factors and governance on audit technology performance - Veerankutty, Farida (2018)
This study attempts to investigate issues faced by public sector auditors over underutilisation of audit technology, which has resulted insufficient progress in technology enabled auditing by the auditors. The under-utilisation of audit technology was also due to ineffective technology related strategies and policies to support the efficient audit. This study has researched on how auditors would be able to enhance successful utilisation of audit technology (i.e., audit technology performance) by looking into the success factors (i.e., auditors attributes, auditor competencies, technology attribute, technology readiness, organisation readiness, professional conduct, client system, client readiness and institutional support). Importantly, this study examined the moderating role of IT Governance on audit technology performance. By drawing on IT Audit Quality Framework and further supported with Diffusion of Innovation Theory and IS Success Model, this study proposes a research framework for Audit Technology Performance. The research framework focuses on the relationship between (i) success factors and audit technology performance and (ii) IT Governance practices and audit technology performance. A survey was conducted among 309 public sector auditors from the National Audit Department of Malaysia who are the external auditors to the ministries, government departments and agencies at federal and state level. The data was analysed using PLS-SEM techniques and validation of measurement model and structural model were done. This study shows that IT Governance practices do not have any interaction effects on the relationship between success factors and audit technology performance. The results indicate that success factors namely auditors attributes and technology attributes directly influence the audit technology performance. However, technology readiness and organisation readiness have no significant influence on the audit technology performance. It shows that bureaucratic nature of public sector organisation has affected differently on the audit technology performance due to the centralised and limited resources. Besides, client readiness and client system do not impact the audit technology performance owing to the mandate of the audit profession and the similar accounting system being implemented by the government agencies. Moreover, competencies of auditors do not play an important role in audit technology performance due to different types of IT control evaluation which requires different level of competencies. Institutional support and professional conduct do not influence the technology usage because Malaysian public sector auditors are mandated by the Audit Act and they are the statutory/external auditors for government agencies. Following to that, the study has successfully derived to the theoretical and professional implications of audit practices in public sector. This study provides some insights on the importance of organisation context (i.e., public sector and audit profession) towards the successful utilisation of technology among the auditors.